A surface-reinforced aerogel composite material and preparation method thereof

By forming a reinforced layer of fiber fabric-reinforced aerogel on the surface of the aerogel composite, the problem that aerogel composite cannot withstand under high-speed airflow erosion is solved, and a surface-reinforced aerogel composite with high strength, low thermal conductivity and excellent thermal insulation performance is achieved.

CN119371228BActive Publication Date: 2025-03-07CHANGSHA RONGLAN MACHINERY

Patent Information

Application Number
CN202411976513.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-07
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Existing aerogel composite materials cannot withstand the high-speed airflow erosion on the surface of high-speed aircraft fuselage, and the structural strength is low, making it difficult to be used as a high-temperature thermal insulation material.

Method used

Through resin filling, preform molding, sol impregnation, supercritical drying, high-temperature sintering and other processes, surface-strengthening aerogel composite materials are prepared to form a surface reinforcement layer of fiber fabric-reinforced aerogel, and improve the strength and thermal insulation properties of the material.

Benefits of technology

It realizes the lightweight, high-strength, high-temperature and low-thermal conductivity of aerogel composite materials, can withstand high-speed airflow erosion and significantly improve thermal insulation performance, and is suitable for thermal protection materials in aerospace and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371228B_ABST
    Figure CN119371228B_ABST
Patent Text Reader

Abstract

The present invention discloses a surface-reinforced aerogel composite material and a preparation method thereof. The prepared aerogel has the characteristics of light weight, high temperature resistance, low thermal conductivity, high strength, simple structure, etc., can withstand high temperatures, resist high-speed airflow scouring and exert excellent thermal insulation performance, and can be used as a thermal protection material in the aerospace field and other related fields. It can solve the problem that the structural strength of aerogel composite materials in the prior art is usually 2 to 3 orders of magnitude different from that of corresponding dense materials, and they cannot withstand high-speed airflow scouring on the surface of the fuselage of high-speed aircraft, and therefore cannot be used as heat-proof materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal protection materials, and in particular relates to a surface-reinforced aerogel composite material and a preparation method thereof. Background Art

[0002] New hypersonic aircraft fly at high Mach numbers in the atmosphere, and severe aerodynamic friction is generated on the surface of the fuselage. The force, heat, sound, vibration and other environments are extremely harsh. It is necessary to use thermal protection materials that are lightweight, resistant to high-temperature and high-speed airflow, have excellent thermal insulation properties and good mechanical properties to protect the components in the fuselage and block heat so that the components can operate within a lower temperature range.

[0003] Ceramic thermal insulation tiles are a typical thermal protection material used in space shuttles. At present, some aircraft have adopted ceramic thermal insulation tiles for large-area thermal protection. Ceramic thermal insulation tiles are mainly made of short fibers, high-temperature adhesives, etc. Their thermal conductivity and brittleness are relatively large, making it difficult to form large-sized, complex and special-shaped components, and installation and maintenance are relatively complicated. Another thermal protection solution is to use high-temperature alloys or ceramic-based materials as the thermal protection layer and ceramic fibers (felt) as the thermal insulation layer, which is called a cover-type thermal protection system (TPS). The cover-type thermal protection system usually requires normal reinforcement ribs to install the thermal insulation layer, which will inevitably form thermal bridges. Therefore, the thermal insulation performance needs to be improved. At the same time, the structure is relatively complex and the preparation cycle is long. Ceramic thermal insulation tiles and cover-type TPS are difficult to meet the stringent requirements of new hypersonic aircraft for thermal protection materials.

[0004] Aerogel is a lightweight nanoporous structural material with extremely low room temperature thermal conductivity (0.012W / (m·K)), and is a new type of super thermal insulation material. Oxide aerogel has both high temperature resistance and low thermal conductivity. Due to its high brittleness and low strength, it is difficult to use it directly as a thermal insulation material. Therefore, by introducing fibers as a reinforcing phase to strengthen and toughen it, aerogel composites with greatly improved mechanical properties are prepared, which have been gradually applied as high-temperature thermal insulation materials in aerospace and other fields. However, compared with the corresponding dense materials, the structural strength of aerogel composites usually differs by 2 to 3 orders of magnitude, and cannot withstand the high-speed airflow scouring on the surface of the fuselage of high-speed aircraft, so it cannot be used as a thermal protection material.

[0005] In response to the urgent demand for new hypersonic aircraft, it is necessary to develop a thermal protection material that has the characteristics of light weight, high strength, high temperature erosion resistance, and low thermal conductivity. Summary of the invention

[0006] Aiming at the problem that the structural strength of aerogel composite materials in the prior art is usually 2 to 3 orders of magnitude lower than that of corresponding dense materials, and they cannot withstand the scouring of high-speed airflow on the surface of the fuselage of high-speed aircraft, and therefore cannot be used as heat-proof materials, the present invention provides a surface-reinforced aerogel composite material and a preparation method thereof. The aerogel prepared by the present invention has the characteristics of light weight, high temperature resistance, low thermal conductivity, high strength, simple structure, etc., can withstand high temperatures, resist the scouring of high-speed airflow and exert excellent thermal insulation performance, and can be used as a heat protection material in the aerospace field and other related fields.

[0007] The technical solution of the present invention is as follows:

[0008] The present invention realizes the preparation of surface-reinforced aerogel composite materials by adopting processes such as resin filling, preform molding, sol impregnation, supercritical drying, and high-temperature sintering.

[0009] The preparation method of the invention comprises six steps: resin filling, preform forming, sol impregnation and aging, supercritical drying, aerogel multiple compounding and high temperature sintering.

[0010] The purpose of the present invention is achieved through the following technical solutions:

[0011] A method for preparing a surface-reinforced aerogel composite material comprises the following steps:

[0012] S1. Resin filling:

[0013] After the resin is melted in a reactor at 40°C to 160°C, a curing agent is added and stirred evenly to form a low-viscosity resin liquid; under a pressure of -0.1MPa to 10MPa, the resin liquid is impregnated into an aerogel composite material, and after being maintained at a set pressure for 2h to 10h, it is heated to 40°C to 350°C and maintained for 4h to 24h to undergo a curing and cross-linking reaction to obtain a resin-filled aerogel;

[0014] The resin is one of epoxy resin, phenolic resin, polyimide resin and unsaturated polyester; and the curing method is:

[0015] The curing agent of the epoxy resin is one of imidazole, polyamine, acid anhydride, and polyphthalamide, with a melting temperature of 90°C to 150°C, a curing temperature of 180°C to 260°C, and a mass ratio of curing agent to epoxy resin = (0.3-1):1;

[0016] The curing agent of the phenolic resin is one of hydrochloric acid, phosphoric acid, p-toluenesulfonic acid, phenolsulfonic acid, sodium hydroxide and ammonium hydroxide, the melting temperature is 100°C to 160°C, the curing temperature is 180°C to 260°C, and the mass ratio of the curing agent to the phenolic resin is (0.05-0.20):1;

[0017] The curing of polyimide resin does not require a curing agent, the melting temperature is 100℃~160℃, and the curing temperature is 200℃~350℃;

[0018] The curing agent of the unsaturated polyester is one of ketone peroxide, acyl peroxide, tert-butyl perbenzoate, and peroxycarbonate, with a melting temperature of 40°C to 70°C, a curing temperature of 80°C to 160°C, and a mass ratio of curing agent to unsaturated polyester = (0.005-0.05):1;

[0019] The aerogel composite material is a composite of inorganic fiber and aerogel; the aerogel is one of silicon oxide, aluminum oxide, zirconium oxide aerogel or an aerogel formed by hybridization of any two of them; the inorganic fiber is one of rock wool, glass fiber, quartz fiber, aluminum silicate fiber, zirconium oxide fiber, lanthanum zirconate fiber, aluminum oxide fiber, and mullite fiber;

[0020] S2. Preform forming:

[0021] Punching holes in the resin-filled aerogel obtained in the above step, laying the fiber fabric on the resin-filled aerogel and fitting it in a conformal manner, sewing the fiber fabric and the resin-filled aerogel through the holes of the fiber fabric and the resin-filled aerogel with a fiber thread, and obtaining an aerogel-fiber fabric preform by mold compression molding;

[0022] The punched holes have a hole diameter of 0.5mm-1.5mm and a hole spacing of 5mm-25mm;

[0023] The fiber fabric is one of glass fiber cloth, high silica fiber cloth, quartz fiber cloth, alumina fiber cloth, and mullite fiber cloth, with a thickness of 0.02 mm to 0.4 mm and a number of layers of 5 to 100;

[0024] The fiber wire is one of glass fiber wire, quartz fiber wire, alumina fiber wire and mullite fiber wire, and has a diameter of 0.3 mm to 1.4 mm;

[0025] S3, Sol impregnation and aging:

[0026] Under a pressure condition of -0.1 MPa to 0 MPa, the aerogel-fiber fabric preform is immersed in the sol for 0.5 h to 3 h to obtain a sol-preform mixture, and the sol-preform mixture is maintained at 40° C. to 85° C. for 8 h to 36 h to form a gel-preform composite;

[0027] The sol is one of silicon oxide, aluminum oxide, and zirconium oxide sol or a combination of any two thereof; the solid content of the sol is 5% to 40%, and the solvent used is one of ethanol, methanol, isopropanol, n-propanol, n-butanol, sec-butanol, and tert-butanol;

[0028] S4, Supercritical Drying:

[0029] The gel-preform composite obtained in the above step is subjected to supercritical drying using carbon dioxide as a medium or using an alcohol as a medium to obtain an aerogel-preform composite;

[0030] S5. Aerogel multiple compounding:

[0031] S3-S4 are performed 2 to 7 times to obtain a surface-reinforced aerogel composite body;

[0032] S6, high temperature sintering:

[0033] The surface-reinforced aerogel composite material blank obtained in the above step is placed in a high-temperature furnace, heated from room temperature to 600°C to 1200°C at a heating rate of 1°C / min to 8°C / min, and maintained for 0.5h to 8h, and naturally cooled to obtain a surface-reinforced aerogel composite material. The surface-reinforced aerogel composite material is composed of a surface reinforcement layer and an aerogel composite material, and its structure is as follows: the surface reinforcement layer is a thin layer of fiber fabric reinforced aerogel, which has high strength and can withstand high-temperature airflow scouring to achieve heat protection function; the aerogel composite material is located at the bottom of the surface reinforcement layer, occupies the main thickness, achieves heat insulation and load-bearing functions, and realizes the integration of heat protection and heat insulation functions of the surface-reinforced aerogel composite material;

[0034] The surface-reinforced aerogel composite material includes a quartz fiber reinforced silica aerogel composite material reinforced with quartz fiber cloth reinforced silica aerogel, a zirconia fiber reinforced zirconia aerogel composite material reinforced with quartz fiber cloth reinforced zirconia aerogel, a mullite fiber reinforced alumina aerogel composite material reinforced with alumina fiber cloth reinforced alumina aerogel, and a rock wool reinforced silica aerogel composite material reinforced with glass fiber cloth reinforced silica aerogel;

[0035] The properties of the prepared surface-reinforced aerogel composites are:

[0036] (1) Density: 0.314 g / cm 3 ; After heat treatment at 600℃ for 1h, no interface delamination occurs, and the thickness shrinkage is 0.9%; the thermal conductivity at room temperature is 0.020 W / (m·K), and the thermal conductivity at 600℃ is 0.026 W / (m·K); the compressive strength at 3% deformation is 0.27 MPa, and the bending strength is 14.9 MPa; or:

[0037] (2) Density: 0.362 g / cm 3 -0.394 g / cm 3; After heat treatment at 800℃ for 1h, no interface delamination occurs, and the thickness shrinkage is 0.3%-0.7%; the thermal conductivity at room temperature is 0.025 W / (m·K)-0.026 W / (m·K), and the thermal conductivity at 800℃ is 0.036 W / (m·K)-0.040 W / (m·K); the compressive strength at 3% deformation is 0.47 MPa-0.54 MPa, and the bending strength is 16.7MPa-20.3 MPa; or:

[0038] (3) Density: 0.390 g / cm 3 ; After heat treatment at 1000℃ for 1 h, no interface delamination occurs, and the thickness shrinkage is 0.8%; the thermal conductivity at room temperature is 0.027 W / (m·K), and the thermal conductivity at 1000℃ is 0.035 W / (m·K); the compressive strength at 3% deformation is 0.35 MPa, and the bending strength is 13.3 MPa; or:

[0039] (4) Density: 0.414 g / cm 3 -0.427 g / cm 3 After heat treatment at 1200℃ for 1 h, no interface delamination occurs and the thickness shrinkage is 0.3%; the thermal conductivity at room temperature is 0.033 W / (m·K)-0.034 W / (m·K), and the thermal conductivity at 1200℃ is 0.088 W / (m·K)-0.089 W / (m·K); the compressive strength at 3% deformation is 0.43 MPa-0.46 MPa, and the flexural strength is 14.8MPa-15.4 MPa.

[0040] Furthermore, in step S4, the supercritical drying using carbon dioxide as a medium is performed by placing the gel-preform complex in an autoclave and keeping it sealed, filling the autoclave with carbon dioxide fluid and heating it to above the critical point, and then maintaining it for 6 hours to 20 hours, and then discharging the carbon dioxide fluid until the pressure is 0, thereby obtaining the aerogel-preform complex.

[0041] Furthermore, in step S4, the supercritical drying using an alcohol as a medium is performed by placing the gel-preform composite in an autoclave, adding the alcohol and keeping it sealed, heating it to above the critical point of the alcohol for 1 to 10 hours, and slowly exhausting the gas in the autoclave until the pressure is 0, thereby obtaining an aerogel-preform composite;

[0042] The alcohol substance is one of ethanol, methanol, isopropanol, n-propanol, n-butanol, sec-butanol and tert-butanol, and the volume ratio of the alcohol substance to the gel-preform complex is 1:(0.4-1.8).

[0043] The present invention also relates to a surface-reinforced aerogel composite material, which is obtained by the preparation method of the surface-reinforced aerogel composite material. The surface-reinforced aerogel composite material is composed of a surface-reinforced layer and an aerogel composite material, and its structure is as follows: the surface-reinforced layer is a thin layer of fiber fabric-reinforced aerogel, which has high strength and can withstand high-temperature airflow scouring to achieve a heat-proof function; the aerogel composite material is located at the lower part of the surface-reinforced layer, occupies the main thickness, achieves heat insulation and load-bearing functions, and realizes the integration of heat protection and heat insulation functions of the surface-reinforced aerogel composite material;

[0044] The surface-reinforced aerogel composite material includes a quartz fiber reinforced silica aerogel composite material reinforced with quartz fiber cloth reinforced silica aerogel, a zirconia fiber reinforced zirconia aerogel composite material reinforced with quartz fiber cloth reinforced zirconia aerogel, a mullite fiber reinforced alumina aerogel composite material reinforced with alumina fiber cloth reinforced alumina aerogel, and a rock wool reinforced silica aerogel composite material reinforced with glass fiber cloth reinforced silica aerogel;

[0045] The properties of the prepared surface-reinforced aerogel composites are:

[0046] (1) Density: 0.314 g / cm 3 ; After heat treatment at 600℃ for 1h, no interface delamination occurs, and the thickness shrinkage is 0.9%; the thermal conductivity at room temperature is 0.020 W / (m·K), and the thermal conductivity at 600℃ is 0.026 W / (m·K); the compressive strength at 3% deformation is 0.27 MPa, and the bending strength is 14.9 MPa; or:

[0047] (2) Density: 0.362 g / cm 3 -0.394 g / cm 3 ; After heat treatment at 800℃ for 1h, no interface delamination occurs, and the thickness shrinkage is 0.3%-0.7%; the thermal conductivity at room temperature is 0.025 W / (m·K)-0.026 W / (m·K), and the thermal conductivity at 800℃ is 0.036 W / (m·K)-0.040 W / (m·K); the compressive strength at 3% deformation is 0.47 MPa-0.54 MPa, and the bending strength is 16.7MPa-20.3 MPa; or:

[0048] (3) Density: 0.390 g / cm 3 ; After heat treatment at 1000℃ for 1 h, no interface delamination occurs, and the thickness shrinkage is 0.8%; the thermal conductivity at room temperature is 0.027 W / (m·K), and the thermal conductivity at 1000℃ is 0.035 W / (m·K); the compressive strength at 3% deformation is 0.35 MPa, and the bending strength is 13.3 MPa; or:

[0049] (4) Density: 0.414 g / cm 3 -0.427 g / cm 3 After heat treatment at 1200℃ for 1 h, no interface delamination occurs and the thickness shrinkage is 0.3%; the thermal conductivity at room temperature is 0.033 W / (m·K)-0.034 W / (m·K), and the thermal conductivity at 1200℃ is 0.088 W / (m·K)-0.089 W / (m·K); the compressive strength at 3% deformation is 0.43 MPa-0.46 MPa, and the flexural strength is 14.8MPa-15.4 MPa.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] 1. The surface-reinforced aerogel composite material described in the present invention has the characteristics of low density, high temperature resistance and extremely low thermal conductivity. The fiber fabric reinforced aerogel has the characteristics of low density, high temperature resistance, low thermal conductivity, high strength and high toughness. By forming a layer of fiber fabric reinforced aerogel structure on the surface of the aerogel composite material, the surface of the aerogel composite material is greatly strengthened and can withstand high temperature and high-speed aerogel scouring, thereby realizing the preparation of a lightweight, high temperature resistant, low thermal conductivity and high strength thermal protection material with both heat protection and heat insulation functions.

[0052] 2. The surface-reinforced aerogel composite material described in the present invention has a fiber fabric with excellent temperature resistance and flexibility, and forms a good conformal fit with the aerogel composite material, so that in the subsequent reinforcement process, combined with the molding method, a good interface bonding can be formed between the aerogel composite material and the reinforcement layer, making the two materials an organic, high-strength and tough whole, so that they can withstand harsh thermodynamic environments.

[0053] 3. The preparation method of a surface-reinforced aerogel composite material described in the present invention protects the aerogel composite material by filling nanopores with thermosetting resin, so that the aerogel composite material can maintain its original nanopore structure and thermal insulation performance during the subsequent sol impregnation, supercritical drying, and heat treatment processes; at the same time, the filling of the thermosetting resin can significantly improve the strength of the aerogel composite material, which is beneficial to the subsequent preform molding process, thereby realizing the molding of large-sized complex components. During the heat treatment process, the thermosetting resin filled in the aerogel pores is cleaned, so that the nanopore structure of the aerogel is restored. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.

[0055] Figure 1 This is a process flow chart of a method for preparing a surface-reinforced aerogel composite material according to the present invention;

[0056] Figure 2 is a vertical view of the surface-reinforced aerogel composite material prepared in Example 1 of the present invention;

[0057] Figure 3 is a top view of the surface-reinforced aerogel composite material prepared in Example 1 of the present invention;

[0058] Figure 4 is a scanning electron microscope image (500 μm) of the surface of the strengthening layer in the surface-strengthened aerogel composite material prepared in Example 1 of the present invention;

[0059] Figure 5 is a scanning electron microscope image (50 μm) of the surface of the strengthening layer in the surface-strengthened aerogel composite material prepared in Example 1 of the present invention;

[0060] Figure 6 It is a bending stress-displacement curve diagram of the surface reinforced aerogel composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0061] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] Embodiment 1:

[0063] A method for preparing a surface-reinforced aerogel composite material comprises the following steps:

[0064] S1. Resin filling:

[0065] After the epoxy resin is melted in a reactor at 120°C, polyamine is added and stirred evenly to form a low-viscosity resin liquid; under a pressure of 1.5MPa, the resin liquid is impregnated into a quartz fiber reinforced silica aerogel composite material, maintained at a set pressure for 6 hours, heated to 210°C, maintained for 10 hours to undergo a curing and cross-linking reaction, and a resin-filled aerogel is obtained;

[0066] Polyamine:epoxy resin mass ratio = 0.55:1;

[0067] S2. Preform forming:

[0068] Punching holes in the resin-filled aerogel obtained in the above step, laying a quartz fiber cloth on the resin-filled aerogel to fit the shape, passing a quartz fiber thread through the holes of the quartz fiber cloth and the resin-filled aerogel to sew them, and obtaining an aerogel-fiber fabric preform by mold compression molding;

[0069] The hole diameter is 0.8mm and the hole spacing is 10mm;

[0070] The thickness of the quartz fiber cloth is 0.1 mm, and the number of layers is 10;

[0071] The diameter of the quartz fiber wire is 0.6 mm;

[0072] S3, Sol impregnation and aging:

[0073] Under a pressure of -0.1 MPa, the aerogel-fiber fabric preform is immersed in a silica sol for 2 hours to obtain a sol-preform mixture, and the sol-preform mixture is maintained at 55° C. for 24 hours to form a gel-preform composite;

[0074] The solid content of the silica sol is 13%, and the solvent used is ethanol;

[0075] S4, Supercritical Drying:

[0076] The gel-preform complex obtained in the above step is subjected to supercritical drying using ethanol as a medium, the gel-preform complex is placed in an autoclave, ethanol is added and kept sealed, heated to above the critical point of ethanol and kept for 6 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining an aerogel-preform complex;

[0077] The volume ratio of ethanol to the gel-preform complex was 1:0.8.

[0078] S5. Aerogel multiple compounding:

[0079] S3-S4 were performed 4 times to obtain a surface-reinforced aerogel composite body;

[0080] S6, high temperature sintering:

[0081] The surface-reinforced aerogel composite material blank obtained in the above step is placed in a high-temperature furnace, heated from room temperature to 800°C at a heating rate of 5°C / min, and maintained for 4 hours, and naturally cooled to obtain a surface-reinforced aerogel composite material. The surface-reinforced aerogel composite material is a quartz fiber reinforced silica aerogel composite material reinforced by quartz fiber cloth reinforced silica aerogel. The properties of the prepared surface-reinforced aerogel composite material are as follows:

[0082] Density: 0.362 g / cm 3After heat treatment at 800℃ for 1h, no interface delamination occurs and the thickness shrinkage is 0.7%; the thermal conductivity at room temperature and 800℃ are 0.025W / (m·K) and 0.036 W / (m·K), respectively; the compressive strength at 3% deformation is 0.47MPa, and the bending strength is 16.7MPa.

[0083] Embodiment 2:

[0084] A method for preparing a surface-reinforced aerogel composite material comprises the following steps:

[0085] S1. Resin filling:

[0086] After the phenolic resin is melted in a reactor at 135°C, p-toluenesulfonic acid is added and stirred evenly to form a low-viscosity resin liquid; under a pressure of 3.2MPa, the resin liquid is impregnated into a zirconia fiber reinforced zirconia aerogel composite material, maintained at a set pressure for 6 hours, heated to 225°C, maintained for 12 hours to undergo a curing and cross-linking reaction, and a resin-filled aerogel is obtained;

[0087] p-Toluenesulfonic acid:phenolic resin mass ratio = 0.12:1;

[0088] S2. Preform forming:

[0089] Punching holes in the resin-filled aerogel obtained in the above step, laying a quartz fiber cloth on the resin-filled aerogel to fit the shape, passing a quartz fiber thread through the holes of the quartz fiber cloth and the resin-filled aerogel to sew them, and obtaining an aerogel-fiber fabric preform by mold compression molding;

[0090] The hole diameter is 0.9mm and the hole spacing is 12mm;

[0091] The thickness of the quartz fiber cloth is 0.1 mm, and the number of layers is 10;

[0092] The diameter of the quartz fiber wire is 0.6 mm;

[0093] S3, Sol impregnation and aging:

[0094] Under a pressure condition of -0.08 MPa, the aerogel-fiber fabric preform was immersed in a zirconium oxide sol for 1.5 hours to obtain a sol-preform mixture, and the sol-preform mixture was kept at 60° C. for 15 hours to form a gel-preform composite;

[0095] The solid content of the zirconium oxide sol is 8%, and the solvent used is isopropanol;

[0096] S4, Supercritical Drying:

[0097] The gel-preform complex obtained in the above step is subjected to supercritical drying using isopropanol as a medium, the gel-preform complex is placed in an autoclave, isopropanol is added and kept airtight, heated to above the critical point of ethanol and kept for 5 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining an aerogel-preform complex;

[0098] The volume ratio of isopropanol to the gel-preform complex was 1:1.

[0099] S5. Aerogel multiple compounding:

[0100] S3-S4 were performed 4 times to obtain a surface-reinforced aerogel composite body;

[0101] S6, high temperature sintering:

[0102] The surface-reinforced aerogel composite material blank obtained in the above step is placed in a high-temperature furnace, heated from room temperature to 950°C at a heating rate of 3°C / min, and maintained for 6 hours, and naturally cooled to obtain a surface-reinforced aerogel composite material. The surface-reinforced aerogel composite material is a zirconia fiber-reinforced zirconia aerogel composite material reinforced with quartz fiber cloth-reinforced zirconia aerogel. The properties of the prepared surface-reinforced aerogel composite material are as follows:

[0103] Density: 0.390 g / cm 3 After heat treatment at 1000℃ for 1 h, no interface delamination occurs and the thickness shrinkage is 0.8%; the thermal conductivity at room temperature and 1000℃ is 0.027W / (m·K) and 0.035 W / (m·K), respectively; the compressive strength at 3% deformation is 0.35MPa, and the bending strength is 13.3MPa.

[0104] Embodiment 3:

[0105] A method for preparing a surface-reinforced aerogel composite material comprises the following steps:

[0106] S1. Resin filling:

[0107] The polyimide resin was placed in a reactor at 125°C and melted to form a low-viscosity resin liquid; the resin liquid was impregnated into a mullite fiber reinforced alumina aerogel composite material under a pressure of 1.2 MPa, and after being kept at a set pressure for 4 hours, it was heated to 230°C and kept for 8 hours to undergo a curing and cross-linking reaction to obtain a resin-filled aerogel;

[0108] S2. Preform forming:

[0109] The resin-filled aerogel obtained in the above step is punched, and then the alumina fiber cloth is laid on the resin-filled aerogel to fit the shape, and the alumina fiber wire is passed through the holes of the alumina fiber cloth and the resin-filled aerogel to sew them, and an aerogel-fiber fabric preform is obtained by mold compression molding;

[0110] The hole diameter is 1.2mm and the hole spacing is 15mm;

[0111] The thickness of the alumina fiber cloth is 0.15 mm, and the number of layers is 10;

[0112] The diameter of the alumina fiber wire is 0.9 mm;

[0113] S3, Sol impregnation and aging:

[0114] Under a pressure of -0.1 MPa, the aerogel-fiber fabric preform was immersed in an alumina sol for 2.5 hours to obtain a sol-preform mixture, and the sol-preform mixture was kept at 70° C. for 10 hours to form a gel-preform composite;

[0115] The solid content of the alumina sol is 9.5%, and the solvent used is sec-butyl alcohol;

[0116] S4, Supercritical Drying:

[0117] The gel-preform complex obtained in the above step is subjected to supercritical drying using sec-butanol as a medium, the gel-preform complex is placed in an autoclave, and after adding sec-butanol, it is kept sealed, heated to above the critical point of sec-butanol and maintained for 4.5 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining an aerogel-preform complex;

[0118] The volume ratio of sec-butyl alcohol to the gel-preform complex is 1:1.2.

[0119] S5. Aerogel multiple compounding:

[0120] S3-S4 were performed three times to obtain a surface-reinforced aerogel composite body;

[0121] S6, high temperature sintering:

[0122] The surface-reinforced aerogel composite material blank obtained in the above step is placed in a high-temperature furnace, heated from room temperature to 1100°C at a heating rate of 6°C / min, and maintained for 5 hours, and naturally cooled to obtain a surface-reinforced aerogel composite material. The surface-reinforced aerogel composite material is a mullite fiber-reinforced alumina aerogel composite material reinforced with alumina fiber cloth reinforced alumina aerogel. The properties of the prepared surface-reinforced aerogel composite material are as follows:

[0123] Density: 0.414 g / cm 3 After heat treatment at 1200℃ for 1 h, no interface delamination occurs and the thickness shrinkage is 0.3%; the thermal conductivity at room temperature and 1200℃ are 0.033W / (m·K) and 0.088 W / (m·K), respectively; the compressive strength at 3% deformation is 0.43MPa, and the bending strength is 14.8MPa.

[0124] Embodiment 4:

[0125] A method for preparing a surface-reinforced aerogel composite material comprises the following steps:

[0126] S1. Resin filling:

[0127] After the unsaturated polyester is melted in a reactor at 40°C, ketone peroxide is added and stirred evenly to form a low-viscosity resin liquid; under a pressure of -0.1MPa, the resin liquid is impregnated into a quartz fiber reinforced silica aerogel composite material, maintained at a set pressure for 2 hours, heated to 80°C, maintained for 24 hours to undergo a curing and cross-linking reaction, and a resin-filled aerogel is obtained;

[0128] Ketone peroxide: unsaturated polyester mass ratio = 0.55:1;

[0129] S2. Preform forming:

[0130] Punching holes in the resin-filled aerogel obtained in the above step, laying a quartz fiber cloth on the resin-filled aerogel to fit the shape, passing a quartz fiber thread through the holes of the quartz fiber cloth and the resin-filled aerogel to sew them, and obtaining an aerogel-fiber fabric preform by mold compression molding;

[0131] The hole diameter is 1.5mm and the hole spacing is 25mm;

[0132] The thickness of the quartz fiber cloth is 0.4 mm, and the number of layers is 5;

[0133] The diameter of the quartz fiber wire is 1.4 mm;

[0134] S3, Sol impregnation and aging:

[0135] Under a pressure of 0 MPa, the aerogel-fiber fabric preform is immersed in a silica sol for 3 hours to obtain a sol-preform mixture, and the sol-preform mixture is kept at 40° C. for 36 hours to form a gel-preform composite;

[0136] The solid content of the silica sol is 13%, and the solvent used is ethanol;

[0137] S4, Supercritical Drying:

[0138] The gel-preform complex obtained in the above step is subjected to supercritical drying using ethanol as a medium, the gel-preform complex is placed in an autoclave, ethanol is added and kept sealed, heated to above the critical point of ethanol and kept for 6 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining an aerogel-preform complex;

[0139] The volume ratio of ethanol to the gel-preform complex was 1:1.8.

[0140] S5. Aerogel multiple compounding:

[0141] S3-S4 were performed 5 times to obtain a surface-reinforced aerogel composite body;

[0142] S6, high temperature sintering:

[0143] The surface-reinforced aerogel composite material blank obtained in the above step is placed in a high-temperature furnace, heated from room temperature to 700°C at a heating rate of 8°C / min, and maintained for 8 hours, and naturally cooled to obtain a surface-reinforced aerogel composite material. The surface-reinforced aerogel composite material is a quartz fiber reinforced silica aerogel composite material reinforced by quartz fiber cloth reinforced silica aerogel. The properties of the prepared surface-reinforced aerogel composite material are as follows:

[0144] Density: 0.385 g / cm 3 After heat treatment at 800℃ for 1h, no interface delamination occurs and the thickness shrinkage is 0.5%; the thermal conductivity at room temperature and 800℃ are 0.026W / (m·K) and 0.038 W / (m·K), respectively; the compressive strength at 3% deformation is 0.51 MPa, and the bending strength is 18.2MPa.

[0145] Embodiment 5:

[0146] A method for preparing a surface-reinforced aerogel composite material comprises the following steps:

[0147] S1. Resin filling:

[0148] After the epoxy resin is melted in a reactor at 150°C, imidazole is added and stirred evenly to form a low-viscosity resin liquid; under a pressure of 10MPa, the resin liquid is impregnated into a quartz fiber reinforced silica aerogel composite material, maintained at a set pressure for 2 hours, heated to 260°C, maintained for 4 hours to undergo a curing and cross-linking reaction, and a resin-filled aerogel is obtained;

[0149] Imidazole:epoxy resin mass ratio = 1:1;

[0150] S2. Preform forming:

[0151] The resin-filled aerogel obtained in the above step is punched, and then the high-silica fiber cloth is laid on the resin-filled aerogel to fit the shape, and a quartz fiber line is used to pass through the holes of the high-silica fiber cloth and the resin-filled aerogel to sew them, and an aerogel-fiber fabric preform is obtained by mold compression molding;

[0152] The hole diameter is 0.5mm and the hole spacing is 5mm;

[0153] The thickness of high silica fiber cloth is 0.02mm, and the number of layers is 40;

[0154] The diameter of the quartz fiber wire is 0.3 mm;

[0155] S3, Sol impregnation and aging:

[0156] Under a pressure of -0.1 MPa, the aerogel-fiber fabric preform was immersed in a silica sol for 0.5 h to obtain a sol-preform mixture, and the sol-preform mixture was kept at 60° C. for 14 h to form a gel-preform composite;

[0157] The solid content of the silica sol is 40%, and the solvent used is methanol;

[0158] S4, Supercritical Drying:

[0159] The gel-preform complex obtained in the above step is subjected to supercritical drying using methanol as a medium, the gel-preform complex is placed in an autoclave, methanol is added and kept sealed, heated to above the critical point of methanol and kept for 10 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining an aerogel-preform complex;

[0160] The volume ratio of methanol to the gel-preform complex was 1:0.4.

[0161] S5. Aerogel multiple compounding:

[0162] S3-S4 are performed twice to obtain a surface-reinforced aerogel composite body;

[0163] S6, high temperature sintering:

[0164] The surface-reinforced aerogel composite material blank obtained in the above step is placed in a high-temperature furnace, heated from room temperature to 750°C at a heating rate of 8°C / min, and maintained for 4 hours, and naturally cooled to obtain a surface-reinforced aerogel composite material. The surface-reinforced aerogel composite material is a quartz fiber reinforced silica aerogel composite material reinforced by quartz fiber cloth reinforced silica aerogel. The properties of the prepared surface-reinforced aerogel composite material are as follows:

[0165] Density: 0.394 g / cm 3After heat treatment at 800℃ for 1h, no interface delamination occurs and the thickness shrinkage is 0.3%; the thermal conductivity at room temperature and 800℃ are 0.026W / (m·K) and 0.040 W / (m·K), respectively; the compressive strength at 3% deformation is 0.54 MPa, and the bending strength is 20.3 MPa.

[0166] Embodiment 6:

[0167] A method for preparing a surface-reinforced aerogel composite material comprises the following steps:

[0168] S1. Resin filling:

[0169] The polyimide resin was placed in a reactor at 125°C and melted to form a low-viscosity resin liquid; the resin liquid was impregnated into an alumina fiber reinforced alumina aerogel composite material under a pressure of 3.5 MPa, and after being kept at a set pressure for 6 hours, it was heated to 350°C and kept for 4 hours to undergo a curing and cross-linking reaction to obtain a resin-filled aerogel;

[0170] S2. Preform forming:

[0171] Punching holes in the resin-filled aerogel obtained in the above step, laying a mullite fiber cloth on the resin-filled aerogel to fit the shape, passing a mullite fiber line through the holes of the mullite fiber cloth and the resin-filled aerogel to sew them, and obtaining an aerogel-fiber fabric preform by mold compression molding;

[0172] The hole diameter is 1.0mm and the hole spacing is 20mm;

[0173] The thickness of the mullite fiber cloth is 0.1 mm, and the number of layers is 15;

[0174] The diameter of the mullite fiber wire is 0.8 mm;

[0175] S3, Sol impregnation and aging:

[0176] Under a pressure of -0.1 MPa, the aerogel-fiber fabric preform was immersed in an alumina sol for 2.5 hours to obtain a sol-preform mixture, and the sol-preform mixture was kept at 85° C. for 8 hours to form a gel-preform composite;

[0177] The solid content of the alumina sol is 5%, and the solvent used is n-butanol;

[0178] S4, Supercritical Drying:

[0179] The gel-preform complex obtained in the above step is subjected to supercritical drying using n-butanol as a medium, the gel-preform complex is placed in an autoclave, and after adding n-butanol, it is kept airtight, heated to above the critical point of n-butanol and maintained for 10 hours, and the gas in the autoclave is slowly discharged until the pressure is 0, thereby obtaining an aerogel-preform complex;

[0180] The volume ratio of n-butanol to the gel-preform complex is 1:1.4.

[0181] S5. Aerogel multiple compounding:

[0182] S3-S4 were performed 7 times to obtain a surface-reinforced aerogel composite body;

[0183] S6, high temperature sintering:

[0184] The surface-reinforced aerogel composite material blank obtained in the above step is placed in a high-temperature furnace, heated from room temperature to 1200°C at a heating rate of 1°C / min, and maintained for 0.5h, and naturally cooled to obtain a surface-reinforced aerogel composite material. The surface-reinforced aerogel composite material is one of the mullite fiber-reinforced alumina aerogel composite materials reinforced with alumina fiber cloth reinforced alumina aerogel. The properties of the prepared surface-reinforced aerogel composite material are as follows:

[0185] Density: 0.427 g / cm 3 After heat treatment at 1200℃ for 1 h, no interface delamination occurs and the thickness shrinkage is 0.3%; the thermal conductivity at room temperature and 1200℃ are 0.034W / (m·K) and 0.089W / (m·K), respectively; the compressive strength at 3% deformation is 0.46MPa, and the bending strength is 15.4MPa.

[0186] Embodiment 7:

[0187] A method for preparing a surface-reinforced aerogel composite material comprises the following steps:

[0188] S1. Resin filling:

[0189] After the epoxy resin is melted in a reactor at 120°C, anhydride is added and stirred evenly to form a low-viscosity resin liquid; under a pressure of 1.5MPa, the resin liquid is impregnated into a rock wool reinforced silica aerogel composite material, maintained at a set pressure for 6 hours, heated to 210°C, maintained for 10 hours to undergo a curing and cross-linking reaction, and a resin-filled aerogel is obtained;

[0190] Anhydride: epoxy resin mass ratio = 0.50:1;

[0191] S2. Preform forming:

[0192] Punching holes in the resin-filled aerogel obtained in the above step, laying a glass fiber cloth on the resin-filled aerogel to fit the shape, passing a glass fiber thread through the holes of the glass fiber cloth and the resin-filled aerogel to sew them, and obtaining an aerogel-fiber fabric preform by mold compression molding;

[0193] The hole diameter is 0.8mm and the hole spacing is 10mm;

[0194] The thickness of the glass fiber cloth is 0.1mm, and the number of layers is 10;

[0195] The diameter of the glass fiber wire is 0.6mm;

[0196] S3, Sol impregnation and aging:

[0197] Under a pressure of -0.1 MPa, the aerogel-fiber fabric preform is immersed in a silica sol for 2 hours to obtain a sol-preform mixture, and the sol-preform mixture is maintained at 55° C. for 24 hours to form a gel-preform composite;

[0198] The solid content of the silica sol is 13%, and the solvent used is ethanol;

[0199] S4, Supercritical Drying:

[0200] The gel-preform complex obtained in the above step is subjected to supercritical drying using carbon dioxide as a medium. The gel-preform complex is placed in an autoclave and kept sealed. Carbon dioxide fluid is filled into the autoclave and heated to above the critical point. After maintaining for 16 hours, the carbon dioxide fluid is discharged until the pressure is 0, thereby obtaining an aerogel-preform complex.

[0201] S5. Aerogel multiple compounding:

[0202] S3-S4 were performed 4 times to obtain a surface-reinforced aerogel composite body;

[0203] S6, high temperature sintering:

[0204] The surface-reinforced aerogel composite material blank obtained in the above step is placed in a high-temperature furnace, heated from room temperature to 600°C at a heating rate of 5°C / min, and maintained for 2 hours, and naturally cooled to obtain a surface-reinforced aerogel composite material. The surface-reinforced aerogel composite material is a rock wool-reinforced silica aerogel composite material reinforced with glass fiber cloth-reinforced silica aerogel. The properties of the prepared surface-reinforced aerogel composite material are:

[0205] Density: 0.314 g / cm 3After heat treatment at 600℃ for 1h, no interface delamination occurs and the thickness shrinkage is 0.9%; the thermal conductivity at room temperature and 600℃ are 0.020W / (m·K) and 0.026 W / (m·K), respectively; the compressive strength at 3% deformation is 0.27 MPa, and the bending strength is 14.9 MPa.

[0206] Comparative Example 1:

[0207] The difference between Comparative Example 1 and Example 1 is that the curing temperature of the epoxy resin in step S1 is 100° C., and the rest is the same as Example 1.

[0208] The density of the prepared aerogel composite material is 0.592 g / cm 3 The thermal conductivity coefficients at room temperature and 800℃ are 0.054 and 0.073 W / (m·K) respectively.

[0209] This indicates that the curing temperature is too low, the epoxy resin curing reaction is not sufficient, and the filling density in the aerogel is insufficient, which causes the sol to penetrate into the aerogel pores in the S3 step, and the density and thermal conductivity of the composite material increase significantly.

[0210] Comparative Example 2:

[0211] The difference between Comparative Example 2 and Example 1 is that in step S1, the mass ratio of curing agent:epoxy resin is 0.12:1, and the others are the same as Example 1.

[0212] The density of the prepared aerogel composite material is 0.483 g / cm 3 The thermal conductivity coefficients at room temperature and 800℃ are 0.043 W / (m·K) and 0.059 W / (m·K) respectively.

[0213] This indicates that the mass ratio of the curing agent is low, the epoxy resin curing reaction is insufficient, and the filling density in the aerogel is insufficient, which causes the sol to penetrate into the aerogel pores in the S3 step, and the density and thermal conductivity of the composite material increase.

[0214] Comparative Example 3:

[0215] The difference between Comparative Example 3 and Example 1 is that in step S2, the thickness of the quartz fiber cloth is 1 mm, the number of layers is 1, and the rest is the same as Example 1.

[0216] The density of the prepared aerogel composite material is 0.369 g / cm 3 , the bending strength is 12.4 MPa.

[0217] It shows that if the thickness of the fiber cloth is too large, the interface bonding between the aerogel and the fiber cloth in the surface reinforcement layer will be weakened, as well as the bonding between the aerogel composite material and the surface reinforcement layer, which will significantly affect the bending strength of the material.

[0218] Comparative Example 4:

[0219] The difference between Comparative Example 4 and Example 1 is that the punching spacing in step S2 is 3 mm, and the rest is the same as Example 1.

[0220] The density of the prepared aerogel composite material is 0.381 g / cm 3 The thermal conductivity coefficients at room temperature and 800℃ are 0.028 W / (m·K) and 0.045 W / (m·K) respectively.

[0221] This indicates that a larger punching spacing and a higher longitudinal fiber density will lead to a significant increase in longitudinal heat transfer, thereby increasing the thermal conductivity.

[0222] Comparative Example 5:

[0223] The difference between Comparative Example 5 and Example 5 is that the solid content of the silica sol in step S3 is 50%, and the rest is the same as Example 5.

[0224] The density of the prepared aerogel composite material is 0.341 g / cm 3 , the compressive strength at 3% deformation is 0.27 MPa, and the flexural strength is 7.6 MPa.

[0225] It shows that when the solid content of the sol is too high, its viscosity is relatively large, and the sol is difficult to be fully impregnated, resulting in the surface reinforcement layer being not dense enough and the mechanical properties of the aerogel composite material being greatly reduced.

[0226] Comparative Example 6:

[0227] The difference between Comparative Example 6 and Example 6 is that the solid content of the alumina sol in step S3 is 3%, and the rest is the same as Example 6.

[0228] The density of the prepared aerogel composite material is 0.391 g / cm 3 , the compressive strength at 3% deformation is 0.28 MPa, and the flexural strength is 9.7 MPa.

[0229] It shows that when the solid content of the sol is low, even with the maximum number of impregnation times, it is difficult to ensure the densification of the surface strengthening layer, so that its strengthening effect is greatly reduced and the mechanical properties of the aerogel composite material are significantly reduced.

[0230] Comparative Example 7:

[0231] The difference between Comparative Example 7 and Example 1 is that the normal pressure drying method is adopted in step S4, and the rest is the same as Example 1.

[0232] The prepared aerogel composite material has a certain interface delamination after heat treatment at 800℃ for 1h; the compressive strength at 3% deformation is 0.35 MPa, and the flexural strength is 11.4 MPa.

[0233] This indicates that there is a strong capillary force in the atmospheric pressure drying process, which can easily cause the collapse of the aerogel pore structure and shrinkage cracking, forming hole defects in the surface reinforcement layer, resulting in significantly low mechanical properties of the surface reinforcement layer and the final aerogel composite material.

[0234] Comparative Example 8:

[0235] The difference between Comparative Example 8 and Example 1 is that the sintering temperature in step S6 is 400° C., and the rest is the same as Example 1.

[0236] The prepared aerogel composite material has a compressive strength of 0.33 MPa and a flexural strength of 12.2 MPa.

[0237] This indicates that silica aerogel must be sintered and strengthened between particles at an appropriate temperature. If the sintering temperature is too low, the sintering effect is not obvious, resulting in a decrease in the mechanical properties of the surface strengthening layer.

[0238] Comparative Example 9:

[0239] The difference between Comparative Example 9 and Example 1 is that the sintering temperature in step S6 is 1100° C., and the rest is the same as Example 1.

[0240] The prepared aerogel composite material shrinks and delaminates at the interface after sintering, with a density of 0.548 g / cm 3 ; The thermal conductivity coefficients at room temperature and 800℃ are 0.042 W / (m·K) and 0.077 W / (m·K) respectively.

[0241] This indicates that the sintering temperature is higher than the upper temperature limit of silica aerogel, the aerogel skeleton particles melt and grow, and the pore structure collapses and becomes obviously densified, so that the size of the aerogel composite material shrinks significantly, interface stratification occurs, and the thermal conductivity of the aerogel composite material rises sharply.

[0242] Summary and discussion:

[0243] The surface-reinforced aerogel composite material prepared by the present invention, wherein the surface reinforcement refers to the surface reinforcement layer of the aerogel composite material, and the fiber fabric (one of glass fiber cloth, high silica fiber cloth, quartz fiber cloth, alumina fiber cloth, and mullite fiber cloth) and the fiber wire (one of glass fiber wire, quartz fiber wire, alumina fiber wire, and mullite fiber wire) in the preform forming step are sewn with the resin-filled aerogel to form a preform, and after multiple sol impregnation and aging and supercritical drying treatment, the obtained fiber fabric-reinforced aerogel has a strength much higher than that of the resin-filled aerogel, and is used as the surface reinforcement layer of the aerogel composite material;

[0244] The aerogel composite material refers to a fiber (one of rock wool, glass fiber, quartz fiber, aluminum silicate fiber, zirconium oxide fiber, lanthanum zirconate fiber, aluminum oxide fiber, and mullite fiber) reinforced aerogel (one of silicon oxide, aluminum oxide, and zirconium oxide aerogel or a hybrid of any two of them). Because of its relatively low strength and inability to withstand high-speed airflow scouring, it needs to be surface strengthened.

[0245] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a surface-reinforced aerogel composite material, characterized in that: The following steps are involved: S1. Resin filling: After the resin is melted in a reactor at 40°C to 160°C, a curing agent is added and stirred evenly to form a low-viscosity resin liquid; under a pressure of -0.1MPa to 10MPa, the resin liquid is impregnated into an aerogel composite material, and after being maintained at a set pressure for 2h to 10h, it is heated to 40°C to 350°C and maintained for 4h to 24h to undergo a curing and cross-linking reaction to obtain a resin-filled aerogel; The resin is one of epoxy resin, phenolic resin, polyimide resin and unsaturated polyester; and the curing method is: The curing agent of the epoxy resin is one of imidazole, polyamine, acid anhydride, and polyphthalamide, with a melting temperature of 90°C to 150°C, a curing temperature of 180°C to 260°C, and a mass ratio of curing agent to epoxy resin = (0.3-1):1; The curing agent of the phenolic resin is one of hydrochloric acid, phosphoric acid, p-toluenesulfonic acid, phenolsulfonic acid, sodium hydroxide and ammonium hydroxide, the melting temperature is 100°C to 160°C, the curing temperature is 180°C to 260°C, and the mass ratio of the curing agent to the phenolic resin is (0.05-0.20):1; The curing of polyimide resin does not require a curing agent, the melting temperature is 100℃~160℃, and the curing temperature is 200℃~350℃; The curing agent of the unsaturated polyester is one of ketone peroxide, acyl peroxide, tert-butyl perbenzoate, and peroxycarbonate, with a melting temperature of 40°C to 70°C, a curing temperature of 80°C to 160°C, and a mass ratio of curing agent to unsaturated polyester = (0.005-0.05):1; The aerogel composite material is a composite of inorganic fiber and aerogel; the aerogel is one of silicon oxide, aluminum oxide, zirconium oxide aerogel or an aerogel formed by hybridization of any two of them; the inorganic fiber is one of rock wool, glass fiber, quartz fiber, aluminum silicate fiber, zirconium oxide fiber, lanthanum zirconate fiber, aluminum oxide fiber, and mullite fiber; S2. Preform forming: Punching holes in the resin-filled aerogel obtained in the above step, laying the fiber fabric on the resin-filled aerogel and fitting it in a conformal manner, sewing the fiber fabric and the resin-filled aerogel through the holes of the fiber fabric and the resin-filled aerogel with a fiber thread, and obtaining an aerogel-fiber fabric preform by mold compression molding; The holes have a diameter of 0.5 mm to 1.5 mm and a hole spacing of 5 mm to 25 mm; The fiber fabric is one of glass fiber cloth, high silica fiber cloth, quartz fiber cloth, alumina fiber cloth, and mullite fiber cloth, with a thickness of 0.02 mm to 0.4 mm and a number of layers of 5 to 100; The fiber wire is one of glass fiber wire, quartz fiber wire, alumina fiber wire and mullite fiber wire, and has a diameter of 0.3 mm to 1.4 mm; S3, Sol impregnation and aging: Under a pressure condition of -0.1 MPa to 0 MPa, the aerogel-fiber fabric preform is immersed in the sol for 0.5 h to 3 h to obtain a sol-preform mixture, and the sol-preform mixture is maintained at 40° C. to 85° C. for 8 h to 36 h to form a gel-preform composite; The sol is one of silicon oxide, aluminum oxide, and zirconium oxide sol or a combination of any two thereof; the solid content of the sol is 5% to 40%, and the solvent used is one of ethanol, methanol, isopropanol, n-propanol, n-butanol, sec-butanol, and tert-butanol; S4, Supercritical Drying: The gel-preform composite obtained in the above step is subjected to supercritical drying using carbon dioxide as a medium or using an alcohol as a medium to obtain an aerogel-preform composite; S5. Aerogel multiple compounding: S3-S4 are performed 2 to 7 times to obtain a surface-reinforced aerogel composite body; S6, high temperature sintering: The surface-reinforced aerogel composite material blank obtained in the above step is placed in a high-temperature furnace, heated from room temperature to 600°C to 1200°C at a heating rate of 1°C / min to 8°C / min, and maintained for 0.5h to 8h, and naturally cooled to obtain a surface-reinforced aerogel composite material. The surface-reinforced aerogel composite material is composed of a surface reinforcement layer and an aerogel composite material, and its structure is as follows: the surface reinforcement layer is a thin layer of fiber fabric reinforced aerogel, which has high strength and can withstand high-temperature airflow scouring to achieve heat protection function; the aerogel composite material is located at the bottom of the surface reinforcement layer, occupies the main thickness, achieves heat insulation and load-bearing functions, and realizes the integration of heat protection and heat insulation functions of the surface-reinforced aerogel composite material; The properties of the prepared surface-reinforced aerogel composites are: (1) Density: 0.314 g / cm 3 ; After heat treatment at 600℃ for 1h, no interface delamination occurs, and the thickness shrinkage is 0.9%; the thermal conductivity at room temperature is 0.020 W / (m·K), and the thermal conductivity at 600℃ is 0.026 W / (m·K); the compressive strength at 3% deformation is 0.27MPa, and the bending strength is 14.9MPa; or: (2) Density: 0.362 g / cm 3 -0.394 g / cm 3 ; After heat treatment at 800℃ for 1h, no interface delamination occurs, and the thickness shrinkage is 0.3%-0.7%; the thermal conductivity at room temperature is 0.025 W / (m·K)-0.026 W / (m·K), and the thermal conductivity at 800℃ is 0.036W / (m·K)-0.040 W / (m·K); the compressive strength at 3% deformation is 0.47 MPa-0.54 MPa, and the bending strength is 16.7 MPa-20.3 MPa; or: (3) Density: 0.390 g / cm 3 ; After heat treatment at 1000℃ for 1 h, no interface delamination occurs, and the thickness shrinkage is 0.8%; the thermal conductivity at room temperature is 0.027 W / (m·K), and the thermal conductivity at 1000℃ is 0.035 W / (m·K); the compressive strength at 3% deformation is 0.35 MPa, and the bending strength is 13.3 MPa; or: (4) Density: 0.414 g / cm 3 -0.427 g / cm 3 After heat treatment at 1200℃ for 1 h, no interface delamination occurs and the thickness shrinkage is 0.3%; the thermal conductivity at room temperature is 0.033 W / (m·K)-0.034 W / (m·K), and the thermal conductivity at 1200℃ is 0.088 W / (m·K)-0.089 W / (m·K); the compressive strength at 3% deformation is 0.43 MPa-0.46 MPa, and the flexural strength is 14.8 MPa-15.4MPa.

2. The method for preparing a surface-reinforced aerogel composite material according to claim 1, characterized in that: The supercritical drying using carbon dioxide as a medium described in step S4 is to place the gel-preform complex in an autoclave and keep it sealed, fill the autoclave with carbon dioxide fluid and heat it to above the critical point, keep it for 6h to 20h, then discharge the carbon dioxide fluid until the pressure is 0, and obtain the aerogel-preform complex.

3. The method for preparing a surface-reinforced aerogel composite material according to claim 1, characterized in that: The use of alcohol as a medium for supercritical drying in step S4 is to place the gel-preform complex in an autoclave, add the alcohol and keep it sealed, heat it to above the critical point of the alcohol and keep it for 1 hour to 10 hours, and slowly discharge the gas in the autoclave until the pressure is 0 to obtain the aerogel-preform complex.

4. The method for preparing a surface-reinforced aerogel composite material according to claim 1, characterized in that: The alcohol substance described in step S4 is one of ethanol, methanol, isopropanol, n-propanol, n-butanol, sec-butanol, and tert-butanol, and the volume ratio of the alcohol substance to the gel-preform complex is 1:(0.4-1.8).

5. A surface-reinforced aerogel composite material, characterized in that: The surface-reinforced aerogel composite material is prepared by the preparation method of any one of claims 1 to 4, wherein the surface-reinforced aerogel composite material is composed of a surface-reinforced layer and an aerogel composite material, and its structure is as follows: the surface-reinforced layer is a thin layer of fiber fabric-reinforced aerogel, which has high strength and can withstand high-temperature airflow scouring to achieve heat protection; the aerogel composite material is located at the bottom of the surface-reinforced layer, occupies the main thickness, achieves heat insulation and load-bearing functions, and realizes the integration of heat protection and heat insulation functions of the surface-reinforced aerogel composite material; The properties of the prepared surface-reinforced aerogel composites are: (1) Density: 0.314 g / cm 3 ; After heat treatment at 600℃ for 1h, no interface delamination occurs, and the thickness shrinkage is 0.9%; the thermal conductivity at room temperature is 0.020 W / (m·K), and the thermal conductivity at 600℃ is 0.026 W / (m·K); the compressive strength at 3% deformation is 0.27MPa, and the bending strength is 14.9MPa; or: (2) Density: 0.362 g / cm 3 -0.394 g / cm 3 ; After heat treatment at 800℃ for 1h, no interface delamination occurs, and the thickness shrinkage is 0.3%-0.7%; the thermal conductivity at room temperature is 0.025 W / (m·K)-0.026 W / (m·K), and the thermal conductivity at 800℃ is 0.036W / (m·K)-0.040 W / (m·K); the compressive strength at 3% deformation is 0.47 MPa-0.54 MPa, and the bending strength is 16.7 MPa-20.3 MPa; or: (3) Density: 0.390 g / cm 3 ; After heat treatment at 1000℃ for 1 h, no interface delamination occurs, and the thickness shrinkage is 0.8%; the thermal conductivity at room temperature is 0.027 W / (m·K), and the thermal conductivity at 1000℃ is 0.035 W / (m·K); the compressive strength at 3% deformation is 0.35 MPa, and the bending strength is 13.3 MPa; or: (4) Density: 0.414 g / cm 3 -0.427 g / cm 3 After heat treatment at 1200℃ for 1 h, no interface delamination occurs and the thickness shrinkage is 0.3%; the thermal conductivity at room temperature is 0.033 W / (m·K)-0.034 W / (m·K), and the thermal conductivity at 1200℃ is 0.088 W / (m·K)-0.089 W / (m·K); the compressive strength at 3% deformation is 0.43 MPa-0.46 MPa, and the flexural strength is 14.8 MPa-15.4MPa.

Citation Information

Patent Citations

  • Aerogel heat insulation tool structure and heat insulation plate heat resistance assessment method

    CN111289561A

  • Silicon dioxide aerogel heat shield composite material and manufacturing method therefor

    WO2023202701A1

Cited By

  • Polyimide-silicon oxide composite aerogel material and preparation method thereof

    CN121471573A